The man who fell to Earth - Tevis, Walter S. (Vintage Books, 2022)
Thomas Jerome Newton is an extraterrestrial from the planet Anthea, which has been devastated by a series of nuclear wars, and whose inhabitants are twice as intelligent as human beings. When he lands on Earth - in Kentucky, disguised as a human - it's with the intention of saving his own people from extinction.